Activation of pro-resolving pathways mediate the therapeutic effects of thymosin beta-4 during Pseudomonas aeruginosa-induced keratitis - Wang, Yuxin; Banga, Loveleen; Ebrahim, Abdul Shukkur; Carion, Thomas W.; Sosne, Gabriel; Berger, Elizabeth A. (Frontiers in Immunology, 2024)
Current treatments for bacterial keratitis fail to address the sight-threatening inflammatory host response. Our recent work elucidating the therapeutic mechanisms of adjunctive thymosin beta-4 (Tβ4) in resolving inflammation and infection in bacterial keratitis revealed modulation of effector cell function and enhanced bacterial killing. The current study builds upon the observed effects on effector cell function by investigating the impact of Tβ4 on specialized pro-resolving lipid mediator (SPM) pathways as they play a significant role in inflammation resolution. Using a well-established in vivo model of Pseudomonas aeruginosainduced bacterial keratitis, we assessed key enzymes (5-LOX and 12/15-LOX) involved in SPM pathway activation, SPM end products (lipoxins, resolvins), and receptor levels for these mediators. In vitro validation using LPS-stimulated murine monocyte/MΦ-like RAW 264.7 cells and siRNA to inhibit Tβ4 and LOX enzymes was carried out to complement our in vivo findings.Results from our in vivo and in vitro investigations demonstrated that adjunctive Tβ4 treatment significantly influences enzymes and receptors involved in SPM pathways. Further, Tβ4 alone enhances the generation of SPM end products in the cornea. Our in vitro assessments confirmed that Tβ4-enhanced phagocytosis is directly mediated by SPM pathway activation. Whereas Tβ4enhanced efferocytosis appeared to be indirect. Collectively, these findings suggest that the therapeutic effect of Tβ4 resolves inflammation through the activation of SPM pathways, thereby enhancing host defense and tissue repair. Our research contributes to understanding the potential mechanisms behind Tβ4 immunoregulatory function, pointing to its promising ability as a comprehensive adjunctive treatment for bacterial keratitis.